2014
DOI: 10.1097/pcc.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Development of Learning Objectives and a Validated Testing Tool for Management of Pediatric Mechanical Ventilation*

Abstract: This is the first description of specific learning objectives for management of pediatric mechanical ventilation and the first validated and reliable testing tool for assessing knowledge. This tool could be used by fellowship programs to assess fellow competency and identify knowledge gaps in this area prior to completion of training. Further work must be done to determine the criteria for determination of competency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
0
18
0
2
Order By: Relevance
“…The present study evaluated the self-assessed knowledge of mechanical ventilation held by various groups of physicians. Few studies have evaluated this topic using validated instruments 18 . Studies performed in residency training centers for emergency services have typically revealed that there are no specific educational programs regarding mechanical ventilation 19 - 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study evaluated the self-assessed knowledge of mechanical ventilation held by various groups of physicians. Few studies have evaluated this topic using validated instruments 18 . Studies performed in residency training centers for emergency services have typically revealed that there are no specific educational programs regarding mechanical ventilation 19 - 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the proportion of individuals who answered each question correctly at each of the two time points, and Table S1 (supplementary material) describes the knowledge topic assessed by each question and its correspondence with a list of competencies described in the literature. 18 , 24 The questions with the highest pre-rotation rates of correct answers were those assessing knowledge of how to calculate respiratory system compliance and resistance, of the characteristics of the basic MV modes, of protective ventilation in ARDS, and of permissive hypercapnia. In contrast, the questions regarding the recognition of asynchrony and of risk factors for extubation failure had the lowest pre-rotation rates of correct answers.…”
Section: Resultsmentioning
confidence: 99%
“…We developed a multiple-choice question test based on clinical cases, initially comprising 22 questions. The questions were developed on the basis of lists of competencies and learning objectives in MV in adult individuals, described in the literature, 18 , 24 as well as on the basis of our respiratory ICU residency program. Most questions were based on clinical cases, and a given case could be used for multiple questions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations